PENGARUH CAPITAL ADEQUACY RATIO(CAR), LOAN TO DEPOSIT RATIO(LDR), NON PERFORMING LOAN(NPL) TERHADAP RETURN ON ASSETS(ROA) DI PERUSAHAAN BPD YANG TERDAFTAR DI OTORITAS JASA KEUANGAN PERIODE 2020-2023 - Lela Ayu Kristina Pakpahan; Ribka Greita Sihombing; Nurhasanah Lumban Batu; Thomas Firdaus Hutahaean (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to examine the extent of the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non-Performing Loans (NPL) on Return on Assets (ROA) at Regional Development Banks (BPD) registered with the Financial Services Authority (OJK) during the period 2020-2023. The background of this study is based on the important role of banks as financial institutions that manage public funds, where the financial performance of banks is a key indicator of their operational success. One measure of performance is ROA, which describes the extent to which banks are efficient in managing to generate profits. This study uses an associative quantitative approach, utilizing secondary data in the form of annual financial reports obtained from the official website of the Financial Services Authority (OJK) (https://www.ojk.go.id). The research sample was selected using purposive sampling from 23 BPDs that met the criteria of complete data for four consecutive years. The analysis method used was multiple linear regression, which began with classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) to ensure the accuracy of the model.